Pengaruh Kompetensi Sumber Daya Manusia, Penerapan Standar Akuntansi Pemerintah dan Sistem Akuntansi Keuangan Daerah terhadap Kualitas Laporan Keuangan: Studi pada OPD Kabupaten Simalungun - Ramadhani, Defiana; Halmawati, Halmawati (Jurnal Nuansa Karya Akuntansi, 2023)
This study set out to find out how the use of government accounting standards, regional financial accounting systems, and expertise in human resources all affect the quality of regional financial reports. This study's participants were all 33 Regional Apparatus Organizations (OPD) in the Simalungun Regency. The samples taken in this study were 33 OPD in Simalungun Regency. Each sample each as many as 3 respondents. Respondents in this study were 1 Head of Finance Subdivision, 1 staff member of the finance section, and 1 treasurer at OPD. With a total sample of 99 people. By distributing questionnaires to the relevant respondents, data were gathered. Using SPSS 24, multiple linear regression was used to analyze the data. The findings indicate that the Accounting System for Regional Finance, Government Accounting Standards, and Human Resource Competence all significantly improve the quality of financial reports produced by regional governments. Additionally, the findings indicate that the Accounting System for Regional Finance significantly improves the quality of financial reports produced by regional governments.